2002
DOI: 10.1002/1521-4141(200209)32:9<2418::aid-immu2418>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G inhibits the functions of murine dendritic cells via the PIR-B immune inhibitory receptor

Abstract: Human histocompatibility leukocyte antigen (HLA)‐G is an MHC class Ib molecule that has been proposed to regulate immune responses during pregnancy. One of the possible mechanisms of that modulation is based on its interaction with immunoglobulin‐like transcript (ILT) receptors. In this study, we show that HLA‐G modifies the function of murine dendritic cells via interactions with the paired immunoglobulin‐like inhibitory receptor, a homologue of the human inhibitory receptor ILT4. Triggering of the immune inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
87
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 128 publications
(96 citation statements)
references
References 32 publications
7
87
1
1
Order By: Relevance
“…These data suggest that the reduction in HLA-G-specific CTLs is probably not specific for the pp65 response but is due to inhibitory triggering signals on the induction of antiviral CTL responses in transgenic mice. Further analysis showed that HLA-G modifies the function of murine DCs via interactions with the PIR-B inhibitory receptor, a homologue of the human inhibitory receptor ILT4 (Liang et al, 2002). This is consistent with results obtained in humans, where specific binding of HLA-G tetramers was associated with ILT4 on myelomonocytic cells (Allan et al, 1999).…”
Section: Discussionsupporting
confidence: 87%
“…These data suggest that the reduction in HLA-G-specific CTLs is probably not specific for the pp65 response but is due to inhibitory triggering signals on the induction of antiviral CTL responses in transgenic mice. Further analysis showed that HLA-G modifies the function of murine DCs via interactions with the PIR-B inhibitory receptor, a homologue of the human inhibitory receptor ILT4 (Liang et al, 2002). This is consistent with results obtained in humans, where specific binding of HLA-G tetramers was associated with ILT4 on myelomonocytic cells (Allan et al, 1999).…”
Section: Discussionsupporting
confidence: 87%
“…Under immunosuppressive treatment, Qa-2 might protect the transplants from rejection by inhibiting the function of cells involved in graft rejection, thereby prolonging allograft survival. Some studies have reported that HLA-G inhibits the cytotoxic activity of CD8 + T cells and NK cells (29), the proliferation of CD4 + T cells (30), the cell-cycle progression of alloreactive T cells (31) and the maturation of antigen-presenting cells (32). Some investigators found that HLA-G efficiently induced immunosuppressive T cells (33).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, HLA-G1 protects targets from both NK cell-and CTLmediated lysis, and only few HLA-G1-positive cells are required to exert significant inhibitory effect [15,18]. Furthermore, HLA-G has been shown to impair the maturation of dendritic cells, resulting in prolonged allogeneic skin graft survival [19]. HLA-G leader peptide stabilizes the cell-surface expression of another non-classical HLA class I inhibitory molecule, HLA-E [20].…”
Section: Introductionmentioning
confidence: 99%